2010
DOI: 10.1519/jsc.0b013e3181e3812e
|View full text |Cite
|
Sign up to set email alerts
|

Relation between In-Game Role and Service Characteristics in Elite Women's Volleyball

Abstract: The aim of this study was to determine whether the in-game role of players (setter, outside, middle, or opposite player) in elite women's volleyball is significantly related to the characteristics of their service. The sample consisted of 1,300 service deliveries (total serves for all matches) made by players in the 8 teams participating in 2 Final 4 stages of the Indesit European Champions League. The variables recorded were in-game role of the server, service type, speed of delivery, service area, target zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 7 publications
2
39
4
3
Order By: Relevance
“…Th e studies on women's serve in elite volleyball revealed that women's most preferable serve was the standing fl oat serve (48.6% of all serves). Th e share of the jump fl oat serve in women was surprisingly small (17%) [25]. In the women's teams of the Estonian highest league, the proportion between the tactical fl oat serve and the standing serve was more equal.…”
Section: Discussionmentioning
confidence: 98%
“…Th e studies on women's serve in elite volleyball revealed that women's most preferable serve was the standing fl oat serve (48.6% of all serves). Th e share of the jump fl oat serve in women was surprisingly small (17%) [25]. In the women's teams of the Estonian highest league, the proportion between the tactical fl oat serve and the standing serve was more equal.…”
Section: Discussionmentioning
confidence: 98%
“…Although K0 is usually included in KII, we analysed it independently to better provide a perceptible sequential analysis of the game actions. Two variables were considered in K0: Serve Zone, following the offi cial FIVB rules which divide the court into six diff erent zones (1, 6 and 5 in the back row, as servers are behind one of these three zones), and Serve Type (jump, jump-fl oat or standing) (Quiroga et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of volleyball, some game variables are commonly studied: type and effi cacy of the serve (Quiroga et al, 2010); quality of serve-reception (Afonso, Moraes, Mesquita, Marcelino, & Duarte, 2009); setting zone and quality (Afonso, Mesquita, Marcelino, & Silva, 2010); effi cacy of the attack (based on zone attack tempo) (Araújo et al, 2011). Volleyball is usually considered to encompass fi ve diff erent game complexes (Ks), which are the equivalents to the concept of the sub-system.…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado coincide con estudios precedentes realizados en categorías de formación (García-Tormo, Redondo, Valladares & Morante, 2006;Gil, Moreno, Moreno, García-González & Del Villar, 2010a) y en alto nivel (Callejón, 2006;Moreno, García de Alcaraz, Moreno, Molina & Santos, 2007;Moraes et al, 2008;Quiroga et al, 2010). Además de este resultado, cabe destacar la asociación significativa entre las variables zona de origen y temporalidad, contribuyendo positivamente a la asociación la realización de saques desde zona 5 con el Campeonato de 2010.…”
Section: Discussionunclassified
“…Esto nos hacen pensar, que los jugadores en categorías de formación están dispuestos a asumir un alto nivel de riesgo con la ejecución del saque en salto, ya que el equipo que está en situación de saque se encuentra en una clara desventaja respecto al equipo que se dispone a construir el ataque. Por tanto, la ejecución del saque en salto, a pesar de que presenta un mayor número de errores y de puntos respecto al saque en apoyo (López-Martínez and Palao, 2011), es una herramienta ideal que pretende frustrar la realización de ataques programados por parte del equipo contrario (Moras et al, 2008;Quiroga et al, 2010;Afonso et al, 2012).…”
Section: Discussionunclassified